Acculturation to global consumer culture and environmentally ethical behaviour: the mediating role of environmental consciousness - Belinda Senooane; Johannes Arnoldus Wiid; Nombulelo Dilotsotlhe (Cogent Business & Management)
This study examined the effects of global consumer culture orientation on environmentally ethical behaviour. Drawing on the theoretical foundations of acculturation to global consumer culture (AGCC), the study set out to develop and validate a unique model that examines the mediating effects of environmental consciousness on the relationship between AGCC and environmentally ethical behaviour. Using a sample of 552 consumers in South Africa, the results show that the selected dimensions of AGCC contribute to consumers’ global culture orientation. The findings revealed that AGCC directly predicts environmentally ethical behaviour, but this relationship is significantly enhanced when environmental consciousness is included as a mediator. Global mass media exposure emerged as the strongest contributor to AGCC, while openness and the desire to emulate global consumer culture had the weakest effect. The study contributes to the literature by offering novel insights into AGCC’s role in pro-environmental behaviour within an emerging market context, a perspective often overlooked. The study’s implications for managers include leveraging global mass media to induce environmentally conscious behaviour and embedding environmental consciousness in marketing strategies to promote sustainable consumption. The research underscores the potential for aligning global consumer culture with environmental responsibility, highlighting AGCC’s dual role in fostering pro-environmental behaviour despite its associations with materialism.